Analisis Potensi Pengembangan Pariwisata Air Terjun Kembar dan Dampaknya terhadap Ekonomi di Kabupaten Solok Selatan - Rahman, Aulia; Syarief, Azhari (TSAQOFAH, 2025)
Nature tourism is one of the potential sectors in boosting the regional economy, including in South Solok Regency. Kembar Waterfalls, as a nature tourist attraction, offers great opportunities for sustainable tourism development. However, this potential has not been maximized optimally. This research aims to analyze the potential for developing Kembar Waterfalls in South Solok Regency and its impact on the local economy, especially in the tourism sector. The method used is a mix method using a spatial approach. The research results 1)Kembar Waterfalls have quite large potential, a total potential score of 30 in the medium category. 2) During the 2019-2023 period, the contribution of tourism to South Solok Regency's Gross Domestic Product (GDP) increased from 2.5% to 4.5%. Based on the results of the SWOT analysis, Kembar Waterfall tourism development strategy is focused on increasing accessibility, digital promotion and empowering local communities.